Symbolic Meaning In The Traditional Dance Tua Reta Lo’u At Kajowair Village, Sikka District - Yani, Albertina Reynilda Eka; Maca, Sudirman; Asyrafunnisa, Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2024)
The objective of the research was to find out the types of symbol, and the function of the symbol of the Tua Reta Lo’u dance at Kajowair Village, Sikka District. The method used in this study was a qualitative descriptive by applying the Charles Peirce semiotic theory the Types of Signs: Icon, Index, and Symbol. The types of symbol and the function of the symbol were analysed. Data were collected through observation, interview, video recording, and supporting documents. The results reveal that there were 10 parts of clothes both male and female in the Tua Reta Lo’u dance, 3 parts of traditional music, and 3 parts of movements in the Tua Reta Lo’u dance, had 3 types of signs including: Icon, Index, and Symbol. The clothes symbolized as beauty, protection, courage, mind control, and emotions. The traditional music symbolized of spirit and harmony. Whereas the movements symbolized of the courage, agility, and body balance. The function of the symbol of the clothes to show the strength, courage, and protection to the enemies. The traditional music had the function of the symbol to inspire the dancers and convey the message of the dance. Meanwhile, the had a function of the symbol as an expression of courage, agility, body balance, and showing off guts to the opponents.